Characterisation of biocompatible layers of ZrO28%Y2O used in combination with other ceramics to modify the surface of implants - Darko Veljić; Časlav Lačnjevac; Marko Rakin; Darko Bajić (Zaštita Materijala)
The aim of this study was to deposit multi-functional ZrO28%Y2O3 coating layers using the plasma spray technology and then to characterise such layers. In combination with other biomedical ceramics, this coating is intended for the application in implant surface modification. The examination was focused on the mechanical properties and microstructure layers . Using the atmospheric plasma spraying, duplex ZrO28%Y2O3/Ni22Cr10Al1Y coating system was deposited on the X15Cr13 stainless steel, with two different thicknesses of the bond and ceramic coatings. The microstructure was analysed using an optical microscope, including the assessment of the content of micropores. The morphology of powder particles and ceramic coating surfaces were examined on a scanning electron microscope (SEM). The quality of the ZrO28%Y2O3 layers makes them suitable for the application and combination with other materials to create a system of biomedical or multifunctional coatings.